Ambient air pollution and health impact in China - Dong, Guang-Hui (Advances in experimental medicine and biology, 2017)
This book focuses on the health impacts of air pollution in China, especially the epidemiology-based exposure-response functions for the mortality, morbidity, and hospital admissions for respiratory diseases, cardiovascular diseases, lung cancer, and mental health related to pollution. It also provides the latest estimates of the magnitude of the adverse effects of air pollution on the health of the Chinese population. By providing a better understanding of the impact of air pollution on health, it improves the scientific basis of risk assessment, and also helps governments develop policies and other health protection initiatives to reduce the impacts of air pollution. The book offers environmental scientists, engineers, researchers and students a comprehensive and organized body of information in the area of air pollution.